The Role of Nurses in Addressing Health Disparities: Ethical Considerations and Public Health Implications - Ritawati, Ritawati; Nurhayati, Nurhayati; Supriyanti, Supriyanti; Hanum, Latifah; Desiana, Desiana; Mardhiah , Ainal (Labor Program Studi Pendidikan Sosiologi, 2024)
Health disparities are a global challenge that requires a comprehensive approach in addressing them. This study aims to analyze the role of nurses in addressing health disparities with a focus on ethical considerations and public health implications. The methodology used is a qualitative approach with a systematic literature study, analyzing scientific publications from 2019-2024 through the PubMed, CINAHL, Scopus, and Web of Science databases. Thematic analysis was conducted using the PRISMA framework to identify key themes. The results of the study revealed three main findings: (1) the transformative role of nurses as agents of change in the health system, (2) the complexity of ethical challenges in nursing practice, and (3) significant implications for public health. Analysis through Leininger's transcultural nursing theory and Parsons' structural functional theory shows the importance of integrating cultural understanding with a systemic approach in addressing health disparities. This study provides an important contribution to understanding the role of nurses and developing strategies to address health disparities in the future.